Desenvolvimento de filmes finos de dióxido de estanho depositados via spin-coating e caracterização das propriedades mecânicas e termo-ópticas - Drabeski, Regiane Gordia (2019)
Semiconductor oxides are materials that have been gaining prominence in the current scenario due to their importance in solar panels, gas sensors, among others. The thin films of tin dioxide have great applicability due to their high transparency in the visible range, and for being an abundant material in Brazil. In the present work, solutions of tin dioxide were prepared by the polymeric precursors method (Pechini method) and in these was carried out a pressure-assisted thermal treatment after the film deposition on glass substrate by the spin coating technique. The samples were analyzed by scanning electron microscopy; Raman spectroscopy; photoacoustic spectroscopy; two-beam lag photoacoustic technique; and nanoindentation. Scanning electron microscopy allowed to verify the growth of the SnO2 layers in the substrate and to evaluate the pressure assisted thermal treatment (PATT) influence on the film thickness. Raman spectroscopy has shown that this treatment did not alter the molecules vibration modules. Photoacoustic spectroscopy showed a blueshift in the absorption band for tin dioxide, along with an increase of hydroxyl bands and an increase of the gap energy after PATT. A depth profile indicated a slow photoacoustic signal attenuation relative to tin dioxide up to 140 μm on the substrate for the 5-layersample and with PATT. The phase-resolved photoacoustic method showed a linear increase of the phase difference as function of the higher levels of the factors of the factorial planning, that is, deposition layer increase and pressure assisted thermal treatment. The average effective thermal diffusivity determined by the photoacoustic technique of the two beam lag was =a (0.017 ± 0.001) cm2/s and agree with the literature value for tin dioxide. The samples treated in PATT showed no change in mechanical properties. The statistical analysis pointed out that the five layers with PATT pretended optimal condition to produce a new material with film and substrate interaction and with increased optical properties.